The role of husband support on subjective well-being in working mothers - Prasiska, Nova Nita Anggun; Hudaniah, Hudaniah; Andriany, Devina (Jurnal Ilmiah Psikologi Terapan, 2024)
A mother who decides to work often experiences role conflict because she cannot divide her time to carry out her roles, both as a mother and worker, which can cause stress and low life satisfaction. This has an impact on her subjective well-being. Subjective well-being is a person’s evaluation of their life, including life satisfaction, experienced emotions, and fulfillment. The social support of a spouse or husband is one of the variables that influence it. Therefore, this study aims to determine how much influence the husband’s support has on the subjective well-being of working mothers. This study uses a quantitative design with a simple regression analysis calculation method. The number of samples in this study was 140 participants who were actively involved, obtained through the purposive sampling technique. The scale used to measure the husband’s support was Receipt of Spousal Support Items, while the scale to measure subjective well-being used the Satisfaction with Life Scale (SWLS) and Positive Affect Negative Affect Schedule (PANAS). This study shows that there is an influence of the husband’s support on the 3 aspects of subjective well-being in working mothers with the value of p < 0.01. p (1, 138) = 64.11, F = 0,317, 2R < 0.01 The husband’s support also explained a significant proportion of the variation in positive aspect scores, (138) = 0.027, t= 0.217 p < 0.01. p (1, 138) = 52.71, F = 0,276, R2 < 0.01 The husband’s also explained a significant proportion of the variation in positive affect scores, (138) = 0.038, t= .278. p < 0.01. p (1, 138) = 71.10, F = 3,40, R2 < .01. The husband’s also explained a significant proportion of the variation in negative affect scores, (138) = 0.042, t = 0.-353. The implication of the findings of this study is that the husband’s support is able to balance emotions in a working mother so as to create satisfaction in life, which is an aspect of forming subjective well-being.